Cardiac transplantation in a neonate—First case in Switzerland and European overview. Issue 5 (4th April 2017) - Schweiger, Martin; Stiasny, Brian; Immer, Franz; Bürki, Christoph; Schmiady, Martin; Dave, Hitendu; Cavigelli‐Brunner, Anna; Kretschmar, Oliver; Cannizzaro, Vincenzo; Hübler, Michael
Abstract: Twenty‐four percent of pediatric heart transplantations (pHTx) are carried out in infants. Neonatal heart transplantation is both rarely performed and challenging. We report on a newborn baby girl suffering from cardiac failure due to a huge tumor (24×52 mm) within the free wall of the left ventricle (LV) and subtotal obstruction of the main left bronchus. Following a surgical tumor resection, a Berlin Heart EXCOR left ventricular assist device was implanted as the bridge to the transplantation. In spite of an organ donor/recipient mismatch of >200%, both heart transplantation and the postoperative course were successful. In addition to this case report, the authors also present data from a survey on performed infant and neonatal transplantations in Western Europe. As neonatal heart transplantation is a rare event in Europe, the authors think it is of crucial importance to share this limited experience. We discuss an alternative strategy—namely, palliative surgical correction using the Fontan pathway. The challenges of donor/recipient weight mismatch and the possibilities of overcoming infant donor organ shortage as a postoperative immunosuppressive regimen are discussed as well.